Analisis Perhitungan Harga Pokok Produksi Dengan Metode Activity Based Costing (ABC) Pada PT. Berkat Damai Abadi Medan - Neneng Sri Ningsih (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine the calculation of the cost of production with the Activity Based Costing method at PT. Thanks to the Eternal Peace of Medan. The type of research used in this study is a qualitative research method. With data collection techniques, namely observation, interviews and documentation studies. The analysis technique used is descriptive data analysis technique using Activity Based Costing (ABC) method analysis. The research results show that the calculation of the cost of production at PT. Thanks to Damai Abadi Medan using the traditional method by adding up all fixed costs and variable costs where the traditional system uses the number of units produced as the basis for calculating the cost of production. Determination of Cost of Production based on the Activity-Based Costing System consists of two stages, namely the procedure stage first and second stage procedures. The Activity-Based Costing System uses more Cost Drivers, therefore the Activity-Based Costing System is able to determine more accurate results and does not cause cost distortions. The Activity Based Costing method produces more accurate selling prices for products compared to traditional methods. only cost drivers for all types of products.